2019
DOI: 10.1002/mgg3.695
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in adults with Williams syndrome—A 20‐year follow‐up study

Abstract: Background Williams syndrome (WBS) is a genetic multisystem disorder. The main symptom is borderline (intelligence quotient, IQ 70–79) or abnormally low intelligence (IQ < 70). According to earlier studies young individuals with WBS demonstrate generally a slightly higher verbal IQ (VIQ) compared to performance/nonverbal IQ (PIQ). WBS was recognized as a distinct entity already about 60 years ago, but still cognition in adults with WBS is poorly known. Methods We followed 25 adults (age at baseline 19–68, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…It is commonly understood that cognitive deficits in patients with ID develop during developmental years at individually varying rate regardless of the etiology. Furthermore, the course of cognition could vary depending on the syndrome 12 . In our study, patients were assessed at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly understood that cognitive deficits in patients with ID develop during developmental years at individually varying rate regardless of the etiology. Furthermore, the course of cognition could vary depending on the syndrome 12 . In our study, patients were assessed at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…A 20‐year follow‐up study of people with WS showed that verbal performance strengthened in early adulthood and remained relatively stable up to the age of 45–50 years but then declined rather rapidly. However, the so‐called fluid, non‐verbal abilities were found to remain stable until at least the age of 55 years (Sauna‐aho et al, 2018; Sauna‐aho, Bjelogrlic‐Laakso, Siren, Kangasmäki, & Arvio, 2019). Compared to people with WS, the fluid, non‐verbal cognitive abilities of FXS men seem to decline earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier cross‐sectional as well as longitudinal studies have focused on three genetic syndromes, that is Down, fragile X and William syndromes (Arvio, 2016; Arvio & Luostarinen, 2016; Sauna‐aho et al, 2018, 2019, 2020). The association between Down syndrome and Alzheimer's disease has been known for a long time (Takashima, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1990 s, it has been recognized that adults with intellectual disability who are affected by dementia need special care (Janicki & Keller, 2015; McCarthy & Mullan, 1996). Our earlier studies suggest that the dementia rates in intellectual disability excluding Down syndrome and compared to the general population may be either higher, lower or similar depending on the aetiology of intellectual disability (Arvio, 2016; Arvio & Luostarinen, 2016; Sauna‐aho et al, 2018, 2019, 2020). The purpose of the present cross‐sectional study was to screen dementia signs in different age groups of adults with intellectual disability.…”
Section: Introductionmentioning
confidence: 94%